Wydziedziczenie w prawie polskim i prawie stanu Luizjana - Sobota, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The paper presents the institution of disinheritance in Polish civil law by comparing it with a corresponding institution set forth in the law of Louisiana the USA. The comparative method applied allows the disinheritance examination from a completely different point of view. It is worth mentioning that the mixed legal system is in force in Louisiana, comprising the elements of the continental and common law. The mixed legal systems are nowadays perceived as examples for any codifications in the world.The paper leads to the conclusion that Polish regulation of the disinheritance in the light of rules of proper legislation leaves much to be desired. Polish provisions on disinheritance are misplaced in the Civil Code without separate chapter, their content is insufficient and their application in practice raises many doubts. In this respect, the corresponding provisions of the Louisiana Civil Code outmatch the Polish provisions both in quality and quantity, providing more comprehensive and precise regulation. Comparing these two legal systems, it is desirable to provide a separate chapter in the Civil Code for the institution of disinheritance as well as introduce more detailed and precise provisions— in particular on the reasons for disinheritance.
Keywords: comparative law; Civil Code; Louisiana; disinheritance; will